Klimata Pārmaiņas, Ekoloģija Un Teoloģija. Rosinošas Pārdomas Par Teoloģijas Misiju Mūsdienu Globālo Izaicinājumu Kontekstā: CLIMATE CHANGE, ECOLOGY AND THEOLOGY. EXCITING REFLECTIONS ON THE MISSION OF THEOLOGY IN THE CONTEXT OF CONTEMPORARY GLOBAL CHALLENGES. - Kokins, Ralfs (Cel̜š, 2021)
The purpose of this article is to bring to light the wide and complex range of topics and problems for further reflection on the tasks of theology in the context of current contemporary challenges. In Latvia, there is a noticeable lack of theological discussions pertaining to the areas of rapid climate change, ecology, pollution, resource depletion, overcrowding, quality of life and social ethics. It is crucial for the modern message of the Christian faith to include climatic symbols and to ensure that climate and ecological issues become a matter of course in the fields of theology. Research reveals that in the coming years the main question will not concern restoring the growth, but rather - assuring the basic survival of humanity as such. Therefore, even in this time of global pandemic, theology should not give false hopes for a return to normal (prepandemic) "normality", instead, it should promote a fundamental change in thinking to radically change our attitudes and lifestyles.